Being Mindful About Mindfulness: Exploring the Dark Side - Hall, Sue Parker (International journal of coercion, abuse and manipulation IJCS, 2020)
In this paper, I acknowledge the rising popularity of mindfulness and analyze research into its positive, and less-researched negative, outcomes. I examine concerns about the training, quality, and supervision of mindfulness teachers. I address the roots of mindfulness in Buddhism and the consequences of its secularization, reduction, and commercialization. I argue that the mindfulness intervention works well as a standalone modality, predominantly as a means to manage symptoms and with relatively well clients, but that it is contraindicated with those who have experienced significant life or developmental trauma. I discuss the potential for the abuse of mindfulness in terms of its use in military conflict, recruitment of people into cults, and the purpose of influencing people to accept and tolerate oppressive environments. I make a case for combining psychotherapy and psychoeducation with mindfulness to create a safer and more effective therapeutic process that can support clients, including former members, with more complex trauma issues.